Penguatan Integritas Akademik Mahasiswa melalui Literasi Digital dan Etika - Alhamuddin, Alhamuddin; Arif Hakim; Giantomi Muhammad (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
The message of digitalization in various sectors, including education, makes the learning process feel easy. The ease of access to learning today does not lead to actions that violate academic ethics. These violations are committed massively and generally rely on artificial intelligence. This is a highly ironic phenomenon amidst the rapid development of technology, which should be applied to positive activities, but instead has the opposite effect. Therefore, this study aims to analyze the strengthening of academic integrity through digital literacy and ethics. Using a qualitative approach with descriptive analysis methods, it was conducted at the Faculty of Tarbiyah and Teacher Training, Bandung Islamic University. The research sources were 35 students of the Islamic Religious Education Study Program. Data collection techniques used were interviews, observation, and documentation. Data analysis techniques used were reduction, interpretation, summarization, and conclusions. The results revealed that upholding the academic integrity of Unisba PAI students emphasizes the wise use of AI, accompanied by digital literacy and ethics that maintain reasoning power, honesty, and academic etiquette based on Islamic values. A commitment to transparency in AI use, source verification, and media ethics are the foundation for creating an academic ecosystem with integrity and benefits.